DIRECTNESS IN POLITENESS OF INDONESIAN CHILDREN’S REQUESTS - Elvi Syahrin (BAHAS, 2015)
The role of politeness in social interaction and conversation has been an important topic in sociology and conversational studies. Politeness has become a highly prolific research field in linguistics (Hickey & Stewart 2005). However a comprehensive study has rarely been done on the politeness in children, particularly in Indonesian children. This article is a research-based study that combines pragmatics and speech act issues in language acquisition frame. The study deals with politeness in Indonesian children’s requests in written language. Basing the study on actual written requests produced by children at the age of  9 up to 12 years old, it was found that; (1) the children promote largely direct strategies in their requests to the Bobo magazine, (2) the directness level varies with increasing imposition of children’s requests. The findings indicate the fact that Indonesian children are able to perform politeness in their interaction to others. This findings also call for further study on politeness dealing with subject at different age periods e.g. adolescence, as age factor bears some influence on investigation on these matters. Key word: Directness, politeness, children, requests